The Origins of the Impressionist Concept of the Landscape Series in the Painting of the Middle of the 19th Century - Ivasyutina, Marina A. (Actual Problems of Theory and History of Art, 2013)
The open-air painting and the desire to depict the world in its constant changeability and its motion in time led the impressionists to a new artistic concept — creation of landscape series. Such paintings are combined by the unity of motif, compositional and spatial characteristics into an entire cycle which allows the painters to convey all the subtle changes of Nature depending on the lighting and the time of the day, as it is done, for example, in the famous Claude Monet’s series “Haystacks”, “Poplars”, “Rouen Cathedral”. This article covers the preconditions of a formation of such a concept in the creative activity of the masters of the middle of the 19th c., such as Camille Corot, Gustave Courbet and the painters of the Barbizon school.